Analgesic and gastrointestinal effects of epidural morphine in horses after laparoscopic cryptorchidectomy under general anesthesia. (27th February 2014) - Martin‐Flores, Manuel; Campoy, Luis; Kinsley, Marc A; Mohammed, Hussni O; Gleed, Robin D; Cheetham, Jonathan
Abstract Objective To evaluate the hypothesis that epidural morphine (0.1 mg kg−1) decreases pain in horses after laparoscopic surgery without adversely affecting gastrointestinal (GI) motility. Study design Randomized clinical trial. Animals Eighteen horses undergoing laparoscopic cryptorchidectomy under general anesthesia. Methods Horses were randomly assigned to receive either epidural morphine (0.1 mg kg−1) or no epidural before the start of surgery. Pain behaviors were assessed during the first two post‐operative days using a numerical rating scale. Barium‐filled spheres were administered through a nasogastric tube before anesthesia. GI motility was assessed by recording manure production, by quantitating the spheres in the manure, and by abdominal auscultation of intestinal sounds. Heart rates and cortisol concentrations were also measured during the post‐operative period. Results Pain scores increased for 12 hours after surgery in the control group and were significantly higher than in the morphine group for the first 6 hours. Pain scores remained unaltered in the morphine group throughout the observation period. Heart rate and plasma cortisol concentrations did not differ between groups or with time. No signs of colic were observed in any horse. Conclusion and clinical relevance Epidural morphine (0.1 mg kg−1) did not adversely affect GI motility in horses after laparoscopic surgery under general anesthesia.